Relasi Perwakilan: Putra Daerah dan Penguatan Demokrasi Lokal - Aulia Rachman Eka Putra; Mazdan Maftukha Assyayuti; Atikah Nurdzakiyyah; Hatta Muhammad Irsyad (Fakultas Hukum Universitas Islam Indonesia, 2023)
This research aims to analyze: first, setting the requirements for legislative candidates at the regional level; second, representative relations between local people and the strengthening of local democracy. This research uses normative research methods that use statutory and conceptual approaches. The results of the research concluded, first, there is an ideas regarding setting domicile requirements for prospective candidates based on philosophical, juridical and sociological foundations. Second, the representative relationship between a legislative candidate (son of the region) and the strengthening of local democracy is the formation of an emotional relationship that has a positive side both for the community and for the party in order to realize the fulfillment of local community needs and needs that are in accordance with the competence of each region.